Correlation between correctly sized uncuffed endotracheal tube and ultrasonographically determined subglottic diameter in paediatric population - Makireddy, Rekha (Indian J Anaesth, 2020)
BACKGROUND AND AIMS: Conventional age-based formulae often fail to predict correct size of endotracheal tube (ETT). In this study, we evaluated usefulness of ultrasound in determining appropriate tube size and derived a formula which enables us to predict correct tube size. METHODS: A total of 41 American Society of Anesthesiologists' physical status 1 and 2 children in the age group of 2–6 years, undergoing elective surgery under general anaesthesia with uncuffed ETT were included in the study. Ultrasonography (US) was used to measure the subglottic diameter after induction of anaesthesia. The trachea was intubated with an ETT that allowed an audible leak between 15–30 mmHg. Pearson's correlation was used to assess the correlation between US measured subglottic diameter (US-SD) with diameter of ETT used. Linear regression was used to derive a formula for predicting ETT size. RESULTS: We found that US-SD and patient's age correlated well with actual ETT OD (r: 0.83 and 0.84, respectively). Age-based formula, ETT ID = (Age/3) +3.5 [r: 0.81] had better correlation with actual ETT OD than conventional age-based Cole's formula, i.e., ETT ID = Age/4 + 4 [r: 0.77]. Our results enabled us to derive a formula for selecting uncuffed ETT based on US-SD. CONCLUSION: Our study concludes that although US-SD correlates with actual tracheal tube used and may be useful in choosing appropriate size ETT, there was no difference in number of correct predictions of ETT size by US measurement, universal formula, and locally derived formula.